The Effect of Mechanical Cycling and Different Misfit Levels on Vicker's Microhardness of Retention Screws for Single Implant-Supported Prostheses - Assunção, Wirley Goncalves [UNESP]; Pala Jorge, Juliana Ribeiro [UNESP]; Santos, Paulo Henrique dos [UNESP]; Barao, Valentim Adelino Ricardo [UNESP]; Gomes, Erica Alves [UNESP]; Delben, Juliana Aparecida [UNESP] (Wiley-Blackwell, 2011)
Purpose: The aim of this study was to evaluate the effect of mechanical cycling and different misfit levels on Vicker's microhardness of retention screws for single implant-supported prostheses.Materials and Methods: Premachined UCLA abutments were cast with cobalt-chromium alloy to obtain 48 crowns divided into four groups (n = 12). The crowns presented no misfit in group A (control group) and unilateral misfits of 50 mu m, 100 mu m, and 200 mu m in groups B, C, and D, respectively. The crowns were screwed to external hexagon implants with titanium retention screws (torque of 30 N/cm), and the sets were submitted to three different periods of mechanical cycling: 2 x 10(4), 5 x 10(4), and 1 x 10(6) cycles. Screw microhardness values were measured before and after each cycling period. Data were evaluated by two-way ANOVA and Tukey's test (p < 0.05).Results: Mechanical cycling statistically reduced microhardness values of retention screws regardless of cycling periods and groups. In groups A, B, and C, initial microhardness values were statistically different from final microhardness values (p < 0.05). There was no statistically significant difference for initial screw microhardness values (p > 0.05) among the groups; however, when the groups were compared after mechanical cycling, a statistically significant difference was observed between groups B and D (p < 0.05).Conclusions: Mechanical cycling reduced the Vicker's microhardness values of the retention screws of all groups. The crowns with the highest misfit level presented the highest Vicker's microhardness values.
Keywords: Mechanical cycling; retention-screw microhardness; implant-supported prostheses; misfit